Fish assemblages in a small temperate estuary on the Argentinian coast: spatial variation, environmental influence and relevance as nursery area - Solari, Agustín (2015)
The effects of different environmental variables on the fish community structure were evaluated in a small temperate estuary. The biological and environmental data were collected bimonthly between 2007 and 2009 along the main estuarine axis. Multivariate analyses were applied (CLUSTER, SIMPER, CCA) to determine the spatial structure of fish community and to estimate the environmental influence on it. A total of 48 species of "teleost" fishes were observed, with the families Characidae and Sciaenidae presenting the largest number of species, 90% of the catches being juveniles. The fish community was overwhelmingly dominated by one species (Micropogonias furnieri, 88.9%), and only four species contributed more than 1% of total catch (Odontesthes argentinensis 5.4%, Brevoortia aurea 1.1%, Paralonchurus brasiliensis 1.1%, and Mugil platanus 1.0%). Estuarine and freshwater stragglers dominated in number of species, followed by freshwater migrants and marine migrants. Three areas with different fish assemblages, with distinctive species and functional guilds, were defined along the main axis. The occurrence and spatial spread of these areas were linked to spatial variation in salinity, which was consistently influenced by discharge from the Río de la Plata and local precipitation. The results highlight the importance of shallow environments as nursery areas and permit emphasis on their susceptibility to environmental changes.